2019
DOI: 10.1021/acssuschemeng.9b02559
|View full text |Cite
|
Sign up to set email alerts
|

Surface Hydrophobic Treatment of Water-Sensitive DUT-4 Metal–Organic Framework To Enhance Water Stability for Hydrogen Storage

Abstract: Water stability in acidic, neutral, and basic aqueous solutions is quite important for the potential application of metal−organic frameworks. As evidenced by X-ray diffraction and scanning electron microscopy results, the pristine DUT-4 is extremely water sensitive to acidic, neutral, and basic aqueous solutions and undergoes crystal structure and morphology transformation. The pristine DUT-4 nearly loses its porosity and H 2 uptake capacity after being exposed for 6 d. A facile solution-immersion approach was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…The other strategy to improve the water stability of an MOF is by introducing hydrophobic molecules/polymers as hydrophobic coating to increase surface hydrophobicity of the MOF. Sun Qian et al treated DUT-4 with organosilicon (namely hydrophobic-treated (HT) DUT-4) by immersing the MOF in organosilicon heptane solution and found that the MOF's WCA was significantly increased from 13 ± 2 • (pristine DUT-4) to 148 ± 3 • (HT DUT-4) [46]. Water stability of the pristine and HT DUT-4 were evaluated by immersing them in acidic, neutral, and basic aqueous solution at 50 • C for six days.…”
Section: Addition Of Hydrophobic Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…The other strategy to improve the water stability of an MOF is by introducing hydrophobic molecules/polymers as hydrophobic coating to increase surface hydrophobicity of the MOF. Sun Qian et al treated DUT-4 with organosilicon (namely hydrophobic-treated (HT) DUT-4) by immersing the MOF in organosilicon heptane solution and found that the MOF's WCA was significantly increased from 13 ± 2 • (pristine DUT-4) to 148 ± 3 • (HT DUT-4) [46]. Water stability of the pristine and HT DUT-4 were evaluated by immersing them in acidic, neutral, and basic aqueous solution at 50 • C for six days.…”
Section: Addition Of Hydrophobic Coatingmentioning
confidence: 99%
“…Qian et al treated DUT-4 with organosilicon (namely hydrophobic-treated (HT) DUT-4) by immersing the MOF in organosilicon heptane solution and found that the MOF’s WCA was significantly increased from 13 ± 2 ° (pristine DUT-4) to 148 ± 3° (HT DUT-4) [ 46 ]. Water stability of the pristine and HT DUT-4 were evaluated by immersing them in acidic, neutral, and basic aqueous solution at 50 °C for six days.…”
Section: General Improvement Strategies: Enhancing the Water Stability Of Metal-organic Frameworkmentioning
confidence: 99%
“…The increase in ΔH ads with increasing H 2 loading indicates that chemsorption, rather than physisorption, is dominant for H 2 adsorption on PPNs at temperatures over 273 K. The chemisorption of H 2 can be reflected by the irreversible sorption isotherms measured at 273 and 298 K (Figure S8). 43 The H 2 -uptake capacities for S-520 and S-500 at 77 K and 1 atm are superior to or comparable with those of covalent organic frameworks (COFs) such as CTV-COF (0.75−1.23 wt %, S BET 1170−1245 m 2 g −1 ), 31 TpBD (0.7−1.1 wt %, S BET 339−537 m 2 g −1 ), 44 PCTF (0.9−1.86 wt %, S BET 784−2235 m 2 g −1 ), 45 and BLP (0.68−1.30 wt %, S BET 503−1828 m 2 g −1 ), 46 metal−organic frameworks (MOFs) such as Pb-TCPP (1.02 wt %, S BET 713 m 2 g −1 ) 47 and HT DUT-4 (1.03−1.24 wt %, S BET 903.6−983.8 m 2 g −1 ), 48 polymers with intrinsic microporosity (1.04 wt %, S BET 760 m 2 g −1 ), 34 and conjugated microporous polymers (CMPs) such as POP (1.05−1.1 wt %, S BET 1031 m 2 g −1 ), 42 HCMP (0.9−1.1 wt %, S BET 827−842 m 2 g −1 ), 49 and TPOP (0.83−1.07 wt %, S BET 472−810 m 2 g −1 ). 50 As illustrated in Figure 6d, the C and H atoms on the edges are dominant in the wrinkled structure of the PPN fragment with defects.…”
Section: Scheme 1 Formation Mechanism Of Ppn Sheetsmentioning
confidence: 99%
“…Recently, porous metal–organic frameworks (MOFs) have been investigated and synthesized by many scientists and crystallographers, because they have plenty of structures, lots of catalytic sites, high surface areas, tunable pore environments, and outstanding designabilities. MOFs have been widely used as functional materials in many applications, including gas sorption, liquid separation, optical devices, catalysts, and sensors. Up to now, some reported MOFs have been designed and synthesized to capture and catalyze CO 2 and epoxide into cyclic carbonate, because MOFs have many advantages for this reaction. Meanwhile, porous MOFs have been prepared and further used as absorbing materials to capture I 2 , illustrating that MOFs are great potential materials in this field. , However, the poor stability directly restricts the actual application of MOFs for capture and chemical transformation of CO 2 and I 2 sorption. So far, various efficient approaches have been developed and used to enhance the water stability, but they always require fussy modification steps, additional auxiliary materials, and harsh synthetic conditions. From previous reports, some heterometallic organic frameworks with excellent stability have been prepared and implemented in these applications, because they have highly connected metal clusters to enhance the strength of skeletons. , Hence, it is very important to design and prepare such heterometallic organic frameworks as heterogeneous catalysts for the chemical fixation of CO 2 and epoxide, and I 2 sorption.…”
Section: Introductionmentioning
confidence: 99%